Loss of function of the chloroplast membrane K+/H+ antiporters AtKEA1 and AtKEA2 alters the ROS and NO metabolism but promotes drought stress resilience - Sánchez-McSweeney, Antonio (Plant physiology and biochemistry : PPB, 2021)
Copyright © 2021 Elsevier Masson SAS. All rights reserved.